A Study of the Risk Factors Associated with the Death of Surabaya Embarkation Hajj Pilgrims in 2023 - Ityan Nuril Sofia Imamah (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2025)
The Hajj pilgrimage is a highly sought-after act of worship among followers of Islam. The observed increase in the number of Indonesian pilgrims corresponds with the observed increase in the number of pilgrims at risk of death. In 2023, the highest number of deaths in Indonesia occurred at the Surabaya embarkation point. The objective of this study is to identify the factors associated with the death of pilgrims embarking from Surabaya in 2023, based on data from the SISKOHATKES database. A quantitative approach with a retrospective cohort design was employed, analyzing 17,211 pilgrims selected through purposive sampling. Data were assessed using chi-square tests and Cox regression analysis. The findings indicate that age, hypertension, and diabetes mellitus are the most significant factors associated with mortality. These variables showed a statistically significant impact on death, with the following risk ratios: age (p-value = 0.000; RRa = 5.3), hypertension (p-value = 0.000; RRa = 3.7), and diabetes mellitus (p-value = 0.000; RRa = 18.7). The study concludes that age, hypertension, and diabetes mellitus are the primary risk factors for pilgrim mortality from Surabaya in 2023. It is recommended that the Hajj healthcare program adopt a comprehensive strategy encompassing promotive, preventive, curative, and emergency response measures to mitigate these risks.   Keywords: Death, hajj pilgrims, risk factors